2014
DOI: 10.1134/s0006297914070128
|View full text |Cite
|
Sign up to set email alerts
|

MS2 phage ribonucleoproteins as exogenous internal control for RT-qPCR data normalization in gene expression study of developing rat brain

Abstract: The most popular strategy for normalization of RT-qPCR data involves presenting them in comparison with expression of "housekeeping" genes. However, the required stable expression of the control genes is not always achievable. As an alternative, we used ribonucleoprotein phage particles as an exogenous internal control and demonstrated that this type of normalization provides a simple and reliable method for quantification in RT-qPCR experiments. Using phage-based normalization, we analyzed mRNA levels of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The experiment for each postnatal age was run in triplicate and normalized to Gapdh and Actb mRNA levels. We used Actb as an additional housekeeping gene because it has been shown that the mRNA levels remain very steady throughout the development of the whole brain in Wistar rats (Fedoseeva et al, 2014). Three replicates of measurements from the same pool were then averaged, and the fold induction was determined in a ∆∆ C T -based fold-change calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment for each postnatal age was run in triplicate and normalized to Gapdh and Actb mRNA levels. We used Actb as an additional housekeeping gene because it has been shown that the mRNA levels remain very steady throughout the development of the whole brain in Wistar rats (Fedoseeva et al, 2014). Three replicates of measurements from the same pool were then averaged, and the fold induction was determined in a ∆∆ C T -based fold-change calculation.…”
Section: Methodsmentioning
confidence: 99%
“…This research in question reveals that the stability of the GAPDH gene is large in the samples tested. However, there are differences in stability values in the different algorithm used and, besides that, the candidate gene reference varies according to the tissue and experimental condition imposed (Fedoseeva et al, 2014). Considering this information, it is expected that there will be differences in the stability and the level of gene expression in different researches, even if they are performed with animals of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous literature authors found that the utilization of this candidate gene for RT-qPCR normalization is limited, and they used northern blotting for the control probe [87][88][89] . The stability values fluctuate depending on the method utilised, and the candidate gene reference differs depending on the tissue and experimental conditions imposed [90] . Given this knowledge, it is reasonable to predict discrepancies and substantial errors in the stability and degree of gene expression under different experimental settings [91] , even if they are conducted on animals of the same species.…”
Section: Housekeeping Genes and Diabetesmentioning
confidence: 99%